The Contributions of Customer Knowledge and Artificial Intelligence to Customer Satisfaction - Zada, Ibrahim (International Review of Management and Marketing, 2022)
Customer knowledge is critical for business and marketing strategy, and companies are turning to Artificial Intelligence (AI)-based data analysis to better understand user experience and behavior in both product and service sectors. This paper discusses the importance of customer knowledge and the tools for obtaining it using AI-based analysis. While AI-based analysis has many benefits, such as advanced and detailed analytics, it also has many drawbacks, such as privacy and the human-biased factor that the machine can learn from interacting with humans. AI is a delicate marketing technology that should be controlled by humans because it cannot replace humans in customer service, relationship management, and critical situations.